ANALISIS NILAI KEARIFAN LOKAL DALAM BUKU PEMBELAJARAN TEMATIK SD NEGERI 105277 HAMPARAN PERAK - Muliati Sari; Zon Saroha Ritonga (REKOGNISI : Jurnal Pendidikan dan Kependidikan, 2021)
This research is entitled "Analysis of Learning Difficulties in the Distance This study aims to analyze and explain how: (1)The values of local wisdom in thematic learning books themes 6, 7, 8. (2)The use of local wisdom values in thematic learning books themes 6, 7, 8. The form of this research is qualitative research with content analysis. The research method used is descriptive qualitative. The data of this research is the value of local wisdom in the thematic learning books. The data sources used in this study were thematic books with themes 6, 7, and 8. The data collection techniques used in this study were analysis, documentation, and interviews. The analysis technique used is content analysis. The results of this study reveal several things from the thematic learning books, namely: (1) The values of local wisdom in the thematic learning books produce 14 data by dividing 4 data on theme 6, 7, 8 data on theme 7, and 2 data on theme 8. (2) Benefits the values of local wisdom that can be used as alternative teaching materials, especially thematic learning for class IV SD Negeri 105277 Hamparan Perak contained in themes 6, 7, 8 are adjusted to the basic competencies developed in the lesson plan.